2017
DOI: 10.1186/s12905-017-0458-z
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of perceptions and experiences of contraceptive use, abortion and post-abortion family planning services (PAFP) in three provinces in China

Abstract: BackgroundThe INPAC project aims to evaluate the effectiveness of integrated post-abortion family planning (PAFP) services into existing hospital based abortion services in China. A qualitative study was conducted in three provinces to contribute to developing effective PAFP services through understanding influences on contraceptive use, experiences of abortion and existing PAFP, and their effect on future contraceptive practices from the perspective of users, in the context of social and institutional change.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 37 publications
0
23
0
8
Order By: Relevance
“…Cultural norms may play a role here as well; for example, in China, LARCs are viewed as a contraception method for older people who already have children rather than younger people. 28 Future work exploring culturally appropriate methods to improve longer term contraception use among Chinese international students in Australia would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural norms may play a role here as well; for example, in China, LARCs are viewed as a contraception method for older people who already have children rather than younger people. 28 Future work exploring culturally appropriate methods to improve longer term contraception use among Chinese international students in Australia would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…More than a half of the induced abortions occurred in places of influx, and this proportion was still growing. Reproductive health guidance, such as non-commercial, reliable information on contraceptive methods, should be easily accessible to the floating population in such places of influx [9].…”
Section: Discussionmentioning
confidence: 99%
“…The propensity to have an abortion has been reported to be associated with increased age, lower levels of income, the level of education, migration status, having at least one child and not using effective contraception, and the type of contraceptive use [6,7,8,9]. However, a few studies have analyzed the status of, and changes in, induced abortion among the floating populations across multiple cities.…”
Section: Introductionmentioning
confidence: 99%
“…Given that contraceptive use is low among Nigerian women, desire of the individual woman not to have a pregnancy termination or a repeat pregnancy termination will impact intention to use contraceptives. Studies have already shown that contraceptive use increases when post-abortion family planning services are provided following pregnancy termination [ 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%